2019
DOI: 10.1063/1.5091503
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of intrinsic magnetic damping in defect-free epitaxial Fe3O4 thin films

Abstract: We have investigated the magnetic damping of precessional spin dynamics in defect-controlled epitaxial grown Fe 3 O 4 (111)/Yttria-stabilized Zirconia (YSZ) nanoscale films by all-optical pump-probe measurements. The intrinsic damping constant of the defect-free Fe 3 O 4 film is found to be strikingly larger than that of the asgrown Fe 3 O 4 film with structural defects. We demonstrate that the population of the first-order perpendicular standing spin wave (PSSW) mode, which is exclusively observed in the defe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…and a heat bath which aligns the magnetization along the field direction. In this atomistic formulation of the sLLG, λ = 0.063 represents the local intrinsic contributions of spin-lattice and spin-electron interactions and is extracted from experimental data for the effective Gilbert damping for magnetite thin films 51 .…”
Section: /16mentioning
confidence: 99%
See 1 more Smart Citation
“…and a heat bath which aligns the magnetization along the field direction. In this atomistic formulation of the sLLG, λ = 0.063 represents the local intrinsic contributions of spin-lattice and spin-electron interactions and is extracted from experimental data for the effective Gilbert damping for magnetite thin films 51 .…”
Section: /16mentioning
confidence: 99%
“…The first term of the sLLG describes the precession of the atomic spins and arises due to their quantum mechanical interaction with the effective magnetic field, and the second term describes direct angular momentum transfer between the spins 11/16 and a heat bath which aligns the magnetization along the field direction. In this atomistic formulation of the sLLG, λ = 0.063 represents the local intrinsic contributions of spin-lattice and spin-electron interactions and is extracted from experimental data for the effective Gilbert damping for magnetite thin films 51 .…”
Section: Atomistic Spin Modelmentioning
confidence: 99%
“…It has been reported that multimode spin wave excitation can lead to enhanced magnetic damping, since the spin waves provide additional channels for the energy dissipation of the Kittel mode. [ 48 ] However, this cannot account for the decrease in damping of the compressive‐strained Co 2 FeSi film, which implies other strain‐related damping mechanism to be explored.…”
Section: Strain Control Of Gilbert Dampingmentioning
confidence: 99%
“…Figure 4b shows the lifetimes of the Kittle modes reflecting the intrinsic Gilbert damping as the external field approaches infinity. [36] From the Kittle mode lifetime τ, [48,49] one can follow to derive the effective damping © 2021 Wiley-VCH GmbH constant α eff using the relation α eff = (2πfτ) −1 . It is noteworthy that the lifetime of the Kittle mode is strongly strain-dependent and so as α eff .…”
Section: Strain Control Of Gilbert Dampingmentioning
confidence: 99%
“…Although the damping constant has been predicted to have small values for magnetite [19], we chose critical damping λ = 1 in this work in order to describe the influence of the APB on the quasi-equilibrium magnetic properties of magnetite. Therefore, we focus on the final magnetization state of our simulations but not on its dynamics.…”
Section: Atomistic Spin Model Of Magnetitementioning
confidence: 99%